2015
DOI: 10.1111/apa.13063
|View full text |Cite
|
Sign up to set email alerts
|

Administering different levels of parenteral phosphate and amino acids did not influence growth in extremely preterm infants

Abstract: The phosphate content of the PN influenced plasma phosphate and plasma calcium levels, but increasing the levels of both phosphate and amino acids did not improve weight gain during the first month of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
1
6
3
3
Order By: Relevance
“…18 Hy pophosphatemia may increase bone resorption in associa tion with bone metabolism in preterm infants. 9 In the present study, 20,21 In our study, the duration of invasive mechanical ventilation was not different between the two groups; however, the prevalence rate of BPD, duration of oxygen therapy, was higher in the hypophosphatemia group compared to that in the control group. Although the effect of hypophosphatemia on the respiratory system remains unclear, hypophosphatemia may cause or exacerbate respiratory failure by interfering with weaning from the mechanical ventilator and impairing the con tractility of the diaphragm.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…18 Hy pophosphatemia may increase bone resorption in associa tion with bone metabolism in preterm infants. 9 In the present study, 20,21 In our study, the duration of invasive mechanical ventilation was not different between the two groups; however, the prevalence rate of BPD, duration of oxygen therapy, was higher in the hypophosphatemia group compared to that in the control group. Although the effect of hypophosphatemia on the respiratory system remains unclear, hypophosphatemia may cause or exacerbate respiratory failure by interfering with weaning from the mechanical ventilator and impairing the con tractility of the diaphragm.…”
Section: Discussioncontrasting
confidence: 38%
“…In addition, few studies have examined whether delayed and lower phosphorus administration causes severe hypophosphatemia in ELBWI who receive www.e-kjp.org Perinatology early amino acid administration. 9 There fore, the present study investigated the incidence of severe hypophosphatemia during the first week after birth, and examined the associated clinical factors (including phosphorus supplementation) and outcomes, …”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the study by Moe et al (1) that assessed the effect of different levels of parenteral phosphate and amino acids on the growth of preterm infants, using body weight as a surrogate for growth.…”
Section: Dear Editormentioning
confidence: 99%
“…Moe et al (1) concluded that parenteral solutions with high amino acids and high phosphate content do not provide higher catch-up growth than solutions with high amino acids and low phosphate content. In addition to the graphical evidence, the authors base this conclusion on the statistical analysis of serial measurements of both serum phosphate and the weight standard score (Z-score).…”
Section: Dear Editormentioning
confidence: 99%
“…Many thanks to Virella et al (1) for the observations in their letter to the editor on our recent paper, which found that administering different levels of parenteral phosphate and amino acids did not influence growth in extremely preterm infants (2).…”
mentioning
confidence: 99%